Soil and water conservation in India: Strategies and research challenges - MANIVANNAN, S.; THILAGAM, V. KASTHURI; KHOLA, O.P S. (Journal of Soil and Water Conservation, 2020)
Soil and water are the most important natural resources that meet all human needs, and protect the environment and the civilization. Ever increasing demands for land and water resources due to burgeoning population cause the degradation of these two precious natural resources. Land degradation is a serious problem in India and out of 329 million hectare (Mha) of total geographical area, 146.8 Mha is reported as degraded. India is losing a huge amount of money in terms of loss of productivity from these degraded lands. Though India receives good amount of annual rainfall (1190 mm), due to enhanced need for domestic, agriculture and industrial developmental activities, over-exploitation and laxity of water resource, it becomes scarce. The declining trend of groundwater level in all parts of the country also indicates that the assured supply of good quality water will become a concern for country’s development. Hence holistic management approach of soil and water resources by linking social and economic development with protection of natural ecosystem is the need of the hour. Creation of inventory on soil and water resources, use of modern technological tools for developing conservation strategies, changes in policy to protect natural resources, development of site specific soil and water conservation measures and involvement of local people in conserving the soil and water resources are the future challenges for the scientists and policy makers. This paper highlights the soil and water conservation strategies and areas to be addressed on priority.